Analisis Sosial Relasi Lintas Iman yang Harmonis di Desa Aek Garut Kecamatan Pandan, Kabupaten Tapanuli Tengah (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Harmony between religious communities can be achieved by remembering that Indonesia is a country rich in culture, so harmony between religious communities can also be expressed in the form of traditional wisdom. The purpose of this study is to determine harmonious interfaith relations in Aek Garut Village, Pandan District, Central Tapanuli Regency. The research method used in this study is descriptive qualitative research about the social analysis of harmonious interfaith relations in Aek Garut Village, Pandan District, Central Tapanuli Regency. The socio-religious life of the people of Aek Garut Village looks very harmonious because this is indicated by the fact that there has never been a conflict between religions in the village. Harmony between religious communities in Aek Garut village creates a peaceful society without conflict and this is because the community wants to maintain harmony. It can be concluded that creating harmony between faiths in Aek Garut Village can be done by treating others with respect by accepting differences as a characteristic of diversity.